PENGARUH VOLUME PERDAGANGAN SAHAM, NILAI TUKAR, INFLASI DAN SUKU BUNGATERHADAP PERGERAKAN IHSG PADA BURSA EFEK INDONESIA - Harnanto Nugroho; Dwi Sudaryati (Jurnal Ekonomi Dan Bisnis, 2015)
The capital market is one of the media that provide investment opportunities for individual and institutional investors. Therefore, the direction and magnitude of movement of the stock market to be a topic ofinterest to academics and market practitioners to learn. Capital markets play an important role in theIndonesian economy, where the value of the Composite Stock Price Index can be a leading economic indicator ina country. Index movement is strongly influenced by investor expectations of the fundamental conditions of thecountry and globally. A new information will affect investors; expectations that ultimately will affect the index.Population and sample in this study was the period of the stock price index from January 1, 2008 until December31, 2010.  The results of this study are stock trading volume, exchange rate, inflation, and interest rates SBIsimultaneously affect the movement of the Composite Stock Price Index. Partial test shows that the stock tradingvolume and inflation does not affect the movement of the IHSG.. Keywords: Stock Trading Volume, Exchange Rate, Inflation, SBI, IHSG.